Biogas - Recent Advances and Integrated Approaches 2021
DOI: 10.5772/intechopen.93231
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Biogas Production and Future Perspective

Abstract: The production of biogas via anaerobic digestion (AD) provides significant benefits over other techniques of bioenergy production. Biogas consists of several undesired components, such as H2S, CO2, nitrogen, hydrogen, oxygen, and water vapor, which contribute to lower the calorific value when compared with natural gas. The pollutants founded in low concentration effects the biogas commercial application in large scale, and therefore it must be taken out before usage. Various cleaning and upgrading techniques t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 159 publications
(218 reference statements)
0
7
0
1
Order By: Relevance
“…Some physicochemical and biological technologies include cleaning and upgrading techniques to evaluate the raw biogas quality. Biological methods, cryogenic separation, hydrate separation, membrane enrichment, in situ upgrading, multistage, and high-pressurized anaerobic digestion can be given as examples of advanced modern biogas upgrading techniques . As an example of biogas production from food waste, a study focused on improving the anaerobic digestion process used in biogas production .…”
Section: Novel Approaches For the Valorization Of Agricultural Food W...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some physicochemical and biological technologies include cleaning and upgrading techniques to evaluate the raw biogas quality. Biological methods, cryogenic separation, hydrate separation, membrane enrichment, in situ upgrading, multistage, and high-pressurized anaerobic digestion can be given as examples of advanced modern biogas upgrading techniques . As an example of biogas production from food waste, a study focused on improving the anaerobic digestion process used in biogas production .…”
Section: Novel Approaches For the Valorization Of Agricultural Food W...mentioning
confidence: 99%
“…Biological methods, cryogenic separation, hydrate separation, membrane enrichment, in situ upgrading, multistage, and highpressurized anaerobic digestion can be given as examples of advanced modern biogas upgrading techniques. 39 As an example of biogas production from food waste, a study focused on improving the anaerobic digestion process used in biogas production. 40 They concluded that the practical usage of ultrasound during the pretreatment of food wastes and the anaerobic digestion increase the yield of biogas within a shorter time range.…”
Section: Novel Approaches For the Valorization Ofmentioning
confidence: 99%
“…The Indonesian government recently passed legislation regulating minimum amounts of biogas output from new waste disposal plants under development. [15]…”
Section: Degradation Percentagementioning
confidence: 99%
“…The excess biogas production through anaerobic digestion results in a dramatic increase in effluents, called digestates. This type of by-product is enriched with remarkable levels of nitrogen, phosphorous and organic substances depending on the composition of the substrates used [ 2 ]. After an analysis of 213 different liquid digestates, an average ammonium nitrogen concentration was determined close to 2 g L −1 , forming a C:N ratio of around 6.5, while phosphorus oxide levels were 0.39% w / w , based on digestate fresh weight [ 3 ].…”
Section: Introductionmentioning
confidence: 99%